A Foresight Study on Virtual Reality (VR) in Online Shopping in Malaysia - Ng, Rui De; Shamsuddin, Alina (Research in Management of Technology and Business, 2025)
Virtual Reality (VR) is used to describe a three-dimensional (3D), computer-generated environment which could be explored and interacted with. It is a virtual environment that allowed people to interact from their own places. People entered the virtual world by using VR headsets, which were placed over the eyes and fully immersed them in the virtual environment, creating a realistic experience in the simulation. The environment could be interacted with using hand controllers, gloves with sensors, or the VR headset itself. By using VR in online shopping, it improved the shopping experience for users. The purpose of the study was to identify the issues, challenges, and trends of VR in online shopping, to study the key drivers of VR in online shopping, and to explore the future image of VR in online shopping. The target respondents were selected and mainly covered the users of VR in online shopping, totalling 384 respondents. The research used a combination of qualitative and quantitative methods. This study employed foresight instruments such as STEEPV Analysis and SPSS analysis. STEEPV analysis was used to identify the issues, challenges, and trends of VR in online shopping. SPSS analysis was used to show the result of the key drivers of VR in online shopping in the second phase of the research with impact-uncertainty analysis. Ten key drivers were identified. The approach of impact-uncertainty analysis was used to determine the future image of VR in online shopping. The top two drivers are law and regulation and shopping experience. 384 questionnaires were distributed to the respondents online and the survey return rate was 57.03%. The future image was formed based on the top two drivers and represented the possible future outcomes from 2024 to 2034.The best result using VR in online shopping is Secure and Immersive VR Online Shopping, which means law and regulation are very developed and shopping experience of users are good. This study aimed to help future researchers and developers increase their awareness of adopting VR in online shopping in the future.